EBF recommendation on the validation of bioanalytical methods for dried blood spots. (July 2011) - Timmerman, Philip; White, Steve; Globig, Susanne; Lüüdtke, Silke; Brunet, Leonarda; Smeraglia, John; ,
Over the last few years bioanalysts, pharmacokineticists and clinical investigators have rediscovered the technique of dried blood spots. The revival has provided pharmaceutical R&D a wealth of opportunities to optimize the drug-discovery and development process with respect to animal and patient ethics, new scientific insights and costs savings. On the bioanalytical front, multiple experiments have been performed and a lot of experience has been gained. Nevertheless, the technique still has a number of bioanalytical challenges. The European Bioanalysis Forum discussed the advantages and hurdles of the technique and summarized their current thinking in a recommendation on the validation of bioanalytical methods for dried blood spots, which can be used as a cornerstone for further discussions and experiments.